Development of formulae for estimating amylose content and resistant starch content based on the pasting properties measured by RVA of Japonica polished rice and starch. Issue 2 (1st February 2016) - Nakamura, Sumiko; Katsura, Junji; Kato, Kiyoko; Ohtsubo, Ken'ichi
Abstract: We searched for the easy and simple method to measure the novel indicators which reflect not only AAC, but also (RS) based on pasting properties using RVA. Novel indexes such as SB/Con and Max/Fin (Maximum viscosity/Minimum viscosity) ratios had a very high correlation with proportion of intermediate and long chains of amylopectin; Fb1+2+3 (DP ≧ 13). In Japonica polished rice, estimation formulae for AAC and RS content were developed using novel indexes based on pasting properties by RVA, and these equations showed determination coefficients of 0.89 and 0.80 for calibration and 0.71 and 0.75 for validation test. We developed the estimation formulae for AAC and RS content for Japonica starch samples. These equations showed determination coefficients of 0.86 and 1.00 for calibration and 0.76 and 0.83 for validation test, which showed that these equations can be applied to the unknown rice samples. Graphical abstract: : Formula for estimating the resistant starch.